Living Toward a New Way of Thinking: Re-thinking Introduction to Anthropology Classes by Re-building the Learning Management System. - Wesch, Michael; Klataske, Ryan; Woodward, Tom (Human Organization)
Anthropology is not only a body of knowledge but also a different way of seeing and being in the world that includes persistent inquiry, empathizing, making connections, and opening up to new ideas and experiences. These practices are beneficial in a wide range of careers and for building a meaningful life in a world of persistent change, pluralism, political division, and precarity. Ideally, an introductory course in anthropology would provide a space to inspire and help students practice this way of being in the world. Unfortunately, classrooms, textbooks, and Learning Management Systems often prioritize an information-delivery model of education that places the professor and content at the center. In 2016, we started building anth101.com as an alternative to the traditional textbook and Learning Management System with 10 lessons, 10 challenges, and community features designed to inspire students to live anthropologically. The software development process forced us to interrogate a wide variety of often taken-for-granted elements of virtual learning spaces. While we set out with strong biases against Learning Management Systems, the process gave us an appreciation for what they do well while also revealing structural biases within them that can be overcome with intentional pedagogy.